Identification of new anti-inflammatory agents based on nitrosporeusine natural products of marine origin - Philkhana, Satish Chandra; Verma, Abhishek Kumar; Jachak, Gorakhnath R.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2017)
Nitrosporeusines A and B are two recently isolated marine natural products with novel skeleton and exceptional biological profile. Interesting antiviral activity of nitrosporeusines and promising potential in curing various diseases, evident from positive data from various animal models, led us to investigate their anti-inflammatory potential. Accordingly, we planned and synthesized nitrosporeusines A and B in racemic as well as enantiopure forms. The natural product synthesis was followed by preparation of several analogues, and all the synthesized compounds were evaluated for in vitro and in vivo anti-inflammatory potential. Among them, compounds 25, 29 and 40 significantly reduced levels of nitric oxide (NO), reactive oxygen species (ROS) and pro-inflammatory cytokines. In addition, these compounds suppressed several pro-inflammatory mediators including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nuclear factor-kappa B (NF -kappa B), and thereby can be emerged as potent anti-inflammatory compounds. Furthermore, all possible isomers of lead compound 25 were synthesized, characterized and profiled in same set of assays and found that one of the enantiomer (-)-25a was superior among them. (C) 2017 Elsevier Masson SAS. All rights reserved.